A guide to the performance of James M. Stephenson’s Symphony No. 2: Voices for Concert Band - Peterson, Myron S., author; Phillips, Rebecca L., advisor; Doe, Sue, committee member; Grapes, K. Dawn, committee member; Kenney, Wes, committee member; Leslie, Drew, committee member (Colorado State University. Libraries, 2021)
James M. Stephenson is an American composer whose compositions are lauded by critics, performed on multiple continents, and recognized with prestigious awards from respected intuitions. His Symphony No. 2: Voices for Concert Band won the 2017 National Band Association William D. Revelli Composition Contest, and the 2018 Sousa-ABA-Ostwald Composition Contest. It was commissioned by "The President's Own" United States Marine Band and Colonel Jason Fettig. It was premiered on December 14, 2016 at the Midwest Clinic: International Band and Orchestra Conference at the McCormick Place in Chicago, Illinois. This thesis infuses James M. Stephenson's personal and intimate knowledge of his Symphony No. 2: Voices for Concert Band with a theoretical analysis to provide conductors, performers, and other musically curious patrons insight into understanding its performance. A granular analysis of this symphony examines theoretical topics such as form, melody, harmony, rhythm, dynamics, texture, orchestration, instrumentation, and unifying thematic material. The theoretical analysis then combines insights from Stephenson about the symbolic and emotional development of the piece, along with salient rehearsal considerations. Finally, this paper documents current influences on Stephenson's work and his broader views on composing, composers, and the state of wind bands in general.
Keywords: Stephenson, James; conductor's analysis; Symphony No. 2 Voices